Persepsi Konsumen Terhadap Minat Beli Beras Di Pasar Tradisional Modern (Tramo) Kecamatan Turikale Kabupaten Maros - Amelia, Suci; Imran, Andi Nur; Sadat, Mohammad Anwar (Jurnal Agribis, 2024)
This study aims to determine consumer perceptions of interest in buying rice at the Maros Modern Traditional Market (Tramo) in Turikale District, Maros Regency. The population in this study are all consumers who have shopped for rice at the Maros Modern Traditional Market (Tramo). The number of sources is 30 respondents using an accidental sampling technique. The data analysis technique used is descriptive quantitative. Data analysis uses the method of calculating percentages and intervals. The results showed that consumers' perceptions of interest in buying rice regarding the price variable were in the good perception category, this was due to the fact that the selling price was still within normal limits besides that there were also differences in characteristics between consumers on their buying interest. And regarding consumer perceptions of buying interest regarding the rice quality variable, it is in the good perception category. Because consumers feel that the rice being sold meets the requirements for good quality rice. As for consumer perceptions of buying interest regarding the variable infrastructure of Tramo Market, it is in the very good category. In general, rice consumers show a positive perception of infrastructure. This is reinforced by the large number of consumers who come from various places. And for consumer perceptions of interest in buying rice regarding market location it is in the good category because it is supported by a strategic location and is easily accessible to the public.